Channel Selection Algorithms for Cognitive Radio Systems - Dias, Alexandre Moura Antunes (2020)
The Spectrum of Radio Frequency plays a key/central role in supporting the operation of the whole range of mobile wireless devices. Such centrality derives from the fact it is necessary when operating different technologies, such as TV, cellular networks, and satellite transmissions, among others. Hence, the urgent need to design a better management of these technologies as a means of minimizing the amount spectrum that is used. This study was developed in two different stages. During a preliminary stage we came up with a modelling method of the service time duration in cognitive radio networks, which fosters a better management of the spectrum through its opportunistic use. In a second stage, we propose four algorithms to manage these cognitive radio networks, using the modelling method that was defined in the first stage, as a basis. After implementing all the simulations, it was possible to verify the feasibility of this modelling methodology and also to confirm the expected results. It should also be pointed out that the four suggested algorithms were tested by carrying out simulations, being effective solutions for difference operational scenarios.